2018
DOI: 10.2147/ijn.s155475
|View full text |Cite
|
Sign up to set email alerts
|

Synovitis in mice with inflammatory arthritis monitored with quantitative analysis of dynamic contrast-enhanced NIR fluorescence imaging using iRGD-targeted liposomes as fluorescence probes

Abstract: BackgroundRheumatoid arthritis (RA) is a common inflammatory disorder characterized primarily by synovitis and pannus formation in multiple joints, causing joints destruction and irreversible disability in most cases. Early diagnosis and effective therapy monitoring of RA are of importance for achieving the favorable prognosis.MethodsWe first prepared the targeted fluorescence probes, and then explored the feasibility of near-infrared (NIR) fluorescence molecular imaging to detect and evaluate the RA via the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Live imaging of the differentially-treated RA mice showed that the iELPs accumulated at the arthritic lesions where they were retained for more than 6 hours. Although fluorescence imaging is a reliable and convenient method for monitoring nanoparticle distribution in vivo , it has a short time window which may reduce the accuracy of image-guided therapy 33 . Finally, the iELPs were also biocompatible and showed no systemic toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Live imaging of the differentially-treated RA mice showed that the iELPs accumulated at the arthritic lesions where they were retained for more than 6 hours. Although fluorescence imaging is a reliable and convenient method for monitoring nanoparticle distribution in vivo , it has a short time window which may reduce the accuracy of image-guided therapy 33 . Finally, the iELPs were also biocompatible and showed no systemic toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…13,78,79 This is surprising since the photochemical instability of ICG has been known for long time. 14,15,80,33 We conducted a photobleaching experiment that irradiated a comparative set of ICG liposomes containing three different amounts of α-tocopherol (0, 10, or 20%) and monitored the change in the intensity of ICG absorption and fluorescence signal. The data in Figure 6 (spectral data in Figure S20) shows that ICG photobleaching was substantially attenuated when the liposomes contained 10 or 20% α-tocopherol (compositions 9′ or 10′).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…ICG is an amphiphilic molecule with a propensity to self-aggregate at low micromolar concentrations in water, and its log P has been measured to be 1.81 when the aqueous phase is phosphate buffer (100 mM, pH 7.4) . Over the years, efforts to improve the photophysical and pharmaceutical properties of ICG have investigated numerous nanoparticle formulations. A significant fraction of these nanoparticle formulations are ICG-containing liposomes, and they have been evaluated for various applications in fluorescence imaging and phototherapeutics. , Quite a few published studies have assessed the stability of ICG-containing liposomes by monitoring the change in sample absorbance or fluorescence intensity over time. However, this type of bulk sample measurement does not unambiguously eliminate the possibility of ICG transfer from the liposomes to albumin and related serum proteins within the same sample.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports indicate that Near-infrared fluorescence imaging system with ICG show significant accumulation in inflamed joints with enhanced permeability and retention (EPR), like as the accumulation observed in tumors [29, 30]. Blood vessel insufficiency of inflamed joints in arthritic experimental models increases the leakiness and permeability, which enhances the accumulation of liposomes in arthritic lesion by EPR [31].…”
Section: Methodsmentioning
confidence: 99%